Third-Generation P2Y12 Inhibitors in East Asian Acute Myocardial Infarction Patients: A Nationwide Prospective Multicentre Study - Kang, Jeehoon; Han, Jung-Kyu; Ahn, Youngkeun; Chae, Shung Chull; Kim, Young Jo; Chae, In-ho; Hur, Seung-Ho; Seong, In-Whan; Chae, Jei-Keon; Cho, Myeong Chan; Seung, Ki-Bae; Jeong, Myung Ho; Yang, Han-mo; Park, Kyung Woo; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Hyo-Soo; on behalf of investigators for Korea Acute Myocardial Infarction Registry-National Institute of Health (KAMIR-NIH) (Thrombosis and Haemostasis, 2018)
Third-generation P2Y12 inhibitors (prasugrel, ticagrelor) are recommended in acute myocardial infarction (AMI). We aimed to evaluate the efficacy and safety of third-generation P2Y12 inhibitors in East Asian AMI patients. From the Korean AMI Registry, 9,355 patients who received dual antiplatelet agent (aspirin with clopidogrel [AC], 6,444 [70.5%] patients; aspirin with prasugrel [AP], 1,100 [11.8%] patients; or aspirin with ticagrelor [AT], 1,811 [19.4%] patients) were analysed. In-hospital endpoints were all-cause mortality or bleeding events during admission and 1-year endpoints were major adverse cardiac and cerebrovascular events (MACCE) and major bleeding events. Regarding in-hospital events, AP and AT showed similar all-cause mortality rates but higher bleeding event rates compared with AC. This trend was extended to 1-year endpoints; Cox regression analysis showed that third-generation P2Y12 inhibitors had significantly higher bleeding risk (AP vs. AC: hazard ratio [HR], 2.14; 95% confidence interval [CI], 1.53–2.99; p < 0.001; AT vs. AC: HR, 2.26; 95% CI, 1.73–2.95; p < 0.001). A propensity score matched triplet of 572 patients showed similar 1-year MACCE and higher bleeding events with third-generation P2Y12 inhibitors (2.1 vs. 2.6 vs. 2.1%, p = 0.790 for MACCE and 3.1 vs. 8.0 vs. 8.0%, p < 0.001 for bleeding events, in AC, AP and AT groups, respectively). Inverse probability weighted regression analysis and pooled analysis after randomly imputing missing variables showed consistent results. Collectively, prasugrel and ticagrelor showed similar rates of 1-year MACCE, but a higher rate of bleeding events, compared with clopidogrel in Korean AMI patients. Further studies are warranted to adapt Western guidelines on third-generation P2Y12 inhibitors for East Asians.
Keywords: third-generation P2Y12 inhibitors; clopidogrel; prasugrel; ticagrelor; acute myocardial infarction; east Asian population